Glucocorticoids contribute to metabolic and liver impairments induced by lactation overnutrition in male adult rats - de Souza, Camila F.; Stopa, Larissa Rugila S.; Martins, Andressa B.; Wunderlich, Ana Luiza M.; Lopes, Gabriela Mendicelli; de Fatima Silva, Flaviane; Komino, Ayumi Cristina Medeiros; Zaia, Dimas A. M.; Zaia, Cassia Thaïs B. V.; Lima, Fabio Bessa; Uchoa, Ernane Torres (Frontiers in Physiology, 2023)
Introduction: Lactation overnutrition is a programming agent of energy metabolism, and litter size reduction leads to the early development of obesity, which persists until adulthood. Liver metabolism is disrupted by obesity, and increased levels of circulating glucocorticoids are pointed as a possible mediator for the obesity development, since bilateral adrenalectomy (ADX) can reduce obesity in different models of obesity. Methods: This study aimed to evaluate the effects of glucocorticoids on metabolic changes and liver lipogenesis and insulin pathway induced by lactation overnutrition. For this, on the postnatal day 3 (PND), 3 pups (small litter - SL) or 10 pups (normal litter - NL) were kept with each dam. On PND 60, male Wistar rats underwent bilateral adrenalectomy (ADX) or fictitious surgery (sham), and half of ADX animals received corticosterone (CORT- 25 mg/L) diluted in the drinking fluid. On PND 74, the animals were euthanized by decapitation for trunk blood collection, and liver dissection and storage. Results and Discussion: SL rats presented increased corticosterone, free fatty acids, total and LDL-cholesterol plasma levels, without changes in triglycerides (TG) and HDL-cholesterol. The SL group also showed increased content of liver TG, and expression of fatty acid synthase (FASN), but decreased expression of PI3Kp110 in the liver, compared to NL rats. In the SL group, the ADX decreased plasma levels of corticosterone, FFA, TG and HDL cholesterol, liver TG, and liver expression of FASN, and IRS2, compared to sham animals. In SL animals, CORT treatment increased plasma levels of TG and HDL cholesterol, liver TG, and expression of FASN, IRS1, and IRS2, compared with the ADX group. In summary, the ADX attenuated plasma and liver changes observed after lactation overnutrition, and CORT treatment could reverse most ADX-induced effects. Conclusion: Thus, increased circulating glucocorticoids are likely to play a pivotal role in liver and plasma impairments induced by lactation overnutrition in male rats.